Patient-derived malignant pleural mesothelioma cell cultures: a tool to advance biomarker-driven treatments. Issue 11 (17th September 2020) - Kanellakis, Nikolaos I; Asciak, Rachelle; Hamid, Megat Abd; Yao, Xuan; McCole, Mark; McGowan, Simon; Seraia, Elena; Hatch, Stephanie; Hallifax, Rob J; Mercer, Rachel M; Bedawi, Eihab O; Jones, Stephanie; et al.
Abstract : Malignant pleural mesothelioma (MPM) is an aggressive cancer, associated with poor prognosis. We assessed the feasibility of patient-derived cell cultures to serve as an ex vivo model of MPM. Patient-derived MPM cell cultures (n=16) exhibited stemness features and reflected intratumour and interpatient heterogeneity. A subset of the cells were subjected to high-throughput drug screening and coculture assays with cancer-specific cytotoxic T cells and showed diverse responses. Some of the biphasic MPM cells were capable of processing and presenting the neoantigen SSX-2 endogenously. In conclusion, patient-derived MPM cell cultures are a promising and faithful ex vivo model of MPM.